Experimental and numerical study on the shrinkage-deformation of carrot slices during hot air drying - Jiang, Dalong; Li, Congcong; Lin, Zifan; Wu, Yuntian; Pei, Hongjuan; Zielinska, Magdalena; Xiao, Hongwei (International Journal of Agricultural and Biological Engineering, 2023)
In order to further understand the mechanism of material volume change in the drying process, numerical simulations (considering or neglecting shrinkage) of heat and mass transfer during convective drying of carrot slices under constant and controlled temperature and relative humidity were carried out. Simulated results were validated with experimental data. The results of the simulation show that the Quadratic model fitted well to the moisture ratio and the material temperature data trend with average relative errors of 5.9% and 8.1%, respectively. Additionally, the results of the simulation considering shrinkage show that the moisture and temperature distributions during drying are closer to the experimental data than the results of the simulation disregarding shrinkage. The material moisture content was significantly related to the shrinkage of dried tissue. Temperature and relative humidity significantly affected the volume shrinkage of carrot slices. The volume shrinkage increased with the rising of the constant temperature and the decline of relative humidity. This model can be used to provide more information on the dynamics of heat and mass transfer during drying and can also be adapted to other products and dryers devices. Keywords: carrot drying, numerical simulation, heat, and mass transfer, shrinkage DOI: 10.25165/j.ijabe.20231601.6736 Citation: Jiang D L, Li C C, Lin Z F, Wu Y T, Pei H J, Zielinska M, et al. Experimental and numerical study on the shrinkage-deformation of carrot slices during hot air drying. Int J Agric & Biol Eng, 2023; 16(1): 260–272.